2008
DOI: 10.1111/j.1440-1746.2008.05313.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal resection with a ligation device is an effective and safe treatment for carcinoid tumors in the lower rectum

Abstract: In a large number of cases, ESMR-L proved to be a useful and safe procedure to resect rectal carcinoid tumors 10 mm or less in diameter, especially for those located in the Rb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
110
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 16 publications
6
110
1
1
Order By: Relevance
“…The management and therapy of tumors 1-2 cm in size is controversial, but most will benefit from local treatment, with polypectomy versus band-assisted resection (32)(33)(34). Most of our cases were treated with polypectomy, band-assisted mucosectomy, and TEM.…”
Section: Discussionmentioning
confidence: 99%
“…The management and therapy of tumors 1-2 cm in size is controversial, but most will benefit from local treatment, with polypectomy versus band-assisted resection (32)(33)(34). Most of our cases were treated with polypectomy, band-assisted mucosectomy, and TEM.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 index is known to be a marker of proliferative capacity in cases of breast cancer and other various malignancies (28), while certain authors have noted that Ki-67 is useful for a metastatic index of carcinoid tumors (4,(29)(30)(31). Hotta et al reported that Ki-67 is a reliable microscopic marker to predict the metastatic potential of rectal carcinoids (7).…”
Section: Discussionmentioning
confidence: 99%
“…1 In this retrospective review, they report the results of 63 resections, with complete resection achieved in 95.2% of patients. This is the largest study of endoscopic therapy in the treatment of colorectal carcinoid and supports the growing evidence that these lesions, if properly selected, may be amenable to endoscopic intervention.…”
mentioning
confidence: 99%
“…However, IGT particularly occurs in chronic hepatitis C, alcoholic liver disease and nonalcoholic fatty liver disease so additional mechanisms make significant contributions. 1 Therapies designed to treat IGT aim to prevent diabetes onset. The most common therapy is metformin or acarbose.…”
mentioning
confidence: 99%